STRIVING FOR EXCELLENCE: STUDY OF READINESS TO ORGANIZATIONAL CHANGE IN THE TAX AUTHORITY OF INDONESIA - Hahotan, Siregar Minardo Resky; Desiana, Putri Mega (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The restructuring of organizational structure, along with the improvement of workflow and business processes within the public sector organizations, is conducted to achieve effective and efficient governance. This research utilizes social exchange theory to examine the influence of internal communication satisfaction and perceived organizational support on employee’s readiness to change, mediated by employee engagement to support the renewal of organization in the public sector in Indonesia. The data analysis results from 387 respondents from the Tax Authority employees show that 7 hypotheses have a positive and significant influence, while 3 hypotheses are found to be not significant. The data were gathered via a survey method by sending online questionnaires to the respondents. Using the Lisrel 8.8 program, structural equation modeling (SEM) was used to test the hypotheses.